Health-Improving Rehabilitation Program of Pysical Education at Higher School - V. M. Naskalov (Образование и наука)
The research is aimed to explore the efficiency of innovative technologies and increase the health-improving effect as a result of physical training in ecologically unfavorable conditions. A health-improving rehabilitation program, containing a set of modern means of physical rehabilitation and recreation in combination with physical exercises, was worked out to carry out the pedagogical experiment. The program includes the hydromassage, stretching exercises with biomechanical stimulation and exercises for developing weightlifting abilities. Apart from this, the interval hypoxic training was used in ‘artificially created’ favorable ecological conditions for detoxication. The students at Polotsk State University took part in the experiment. Among the assessment criteria applied by the author, there are generally acknowledged methods identifying the development of physical qualities, external respiration functions, body fat and other components composition. The experiment revealed that the innovative program had enhanced the health-improving effect compared to the traditional training programs, which was expressed by the statistically valid increase of the students’ speed- strength characteristics, flexibility, external respiration functions as well as the body fat decrease. Therefore, in order to increase a health-improving effect of physical training, the author recommends considering the specific ecological and hygienic conditions of a particular region to create the corresponding programs for group and individual health protection and recovery. The research findings can be used in physical education process at universities situated in the regions with unfavorable ecological conditions.